Lithium-based vertically aligned nancomposite films incorporating LixLa0.32(Nb0.7Ti0.32)O3 electrolyte with high Li+ ion conductivity - Adam J. Lovett; Ahmed Kursumovic; Siân Dutton; Zhimin Qi; Zihao He; Haiyan Wang; Judith L. MacManus-Driscoll (APL Materials, 2022)
Vertically aligned nanocomposite (VAN) thin films have shown strong potential in oxide nanoionics but are yet to be explored in detail in solid-state battery systems. Their 3D architectures are attractive because they may allow enhancements in capacity, current, and power densities. In addition, owing to their large interfacial surface areas, the VAN could serve as models to study interfaces and solid-electrolyte interphase formation. Here, we have deposited highly crystalline and epitaxial vertically aligned nanocomposite films composed of a LixLa0.32±0.05(Nb0.7±0.1Ti0.32±0.05)O3±δ-Ti0.8±0.1Nb0.17±0.03O2±δ-anatase [herein referred to as LL(Nb, Ti)O-(Ti, Nb)O2] electrolyte/anode system, the first anode VAN battery system reported. This system has an order of magnitude increased Li+ ionic conductivity over that in bulk Li3xLa1/3−xNbO3 and is comparable with the best available Li3xLa2/3−xTiO3 pulsed laser deposition films. Furthermore, the ionic conducting/electrically insulating LL(Nb, Ti)O and electrically conducting (Ti, Nb)O2 phases are a prerequisite for an interdigitated electrolyte/anode system. This work opens up the possibility of incorporating VAN films into an all solid-state battery, either as electrodes or electrolytes, by the pairing of suitable materials.